2010
DOI: 10.1007/s11661-010-0233-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Content on the Microstructure and Mechanical Properties of Hypereutectoid Steels

Abstract: Hypereutectoid steels with 0, 0.69, 1.29, and 1.95 wt pct aluminum were prepared. The samples were hot rolled at 1100°C followed by cooling in air. The microstructure of the as-rolled samples was characterized using field emission-scanning electron microscopy (FE-SEM). The electron backscattered diffraction (EBSD) technique was used to identify the grain boundary phases. The steels have a pearlitic microstructure with different amounts of grain boundary cementite. A continuous grain boundary cementite network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In order to compare the effects of alloying elements and the cooling rates on the interlamellar spacing of pearlite and the mechanical properties between previous studies and this study, Figure 12 shows the relationship between the tensile strength and the values of interlamellar spacing in previous studies [46,11,14]. The experimental steels in literatures mainly contain Mn and Si, while the amount of Cr is small or few in pearlite steels.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In order to compare the effects of alloying elements and the cooling rates on the interlamellar spacing of pearlite and the mechanical properties between previous studies and this study, Figure 12 shows the relationship between the tensile strength and the values of interlamellar spacing in previous studies [46,11,14]. The experimental steels in literatures mainly contain Mn and Si, while the amount of Cr is small or few in pearlite steels.…”
Section: Resultsmentioning
confidence: 96%
“…While, in this study, the tensile strengths of high-Cr–low-Mn steel are higher than 1500 MPa and the values of interlamellar spacing are thinner than 145 nm, which show an excellent combination between the mechanical properties and microstructures.
Figure 12 The variation of tensile strength of steels versus the interlamellar spacing of pearlite under different compositions and technologies [46,11,14].
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observed partitioning trend is in good agreement with the results reported by other authors [ 10 , 16 ]. On the other hand, in the case of Al-steel, the Al content in cementite is negligible as it could be expected due to its low solubility [ 25 , 26 ]. The concentration of Al in ferrite remains approximately constant and close to the LE values.…”
Section: Resultsmentioning
confidence: 99%
“…Daeubler et al [8] reported that finer pearlite interlamellar and finer prior austenite grain size were beneficial to resisting the surface fatigue crack propagation. The work of Taleff et al [9] and Jang et al [10] indicated the decrease of both pearlite interlamellar spacing and pearlite colony size would increase the tensile strength. It should be noted that the bearing steels need to be subjected to heat treatments after hot rolling.…”
mentioning
confidence: 99%